RANCANG BANGUN SISTEM PENDINGIN DAN PENCUCI PADA MESIN PENGOLAH BIODIESEL DENGAN BAHAN BAKU MINYAK JELANTAH - Rahmawaty, Made; Fauzan, Muhammad Hilmy; Hendriko, Hendriko (Politeknik Negeri Sriwijaya, Indonesia, 2024)
There are three stages for processing biodiesel-based used cooking oil: the esterification process, cooling and purifying FAME, and filtration of crude biodiesel. The time required for purifying FAME is about two until six hours because it has to follow the sedimentation process several times. Therefore, this research developed a biodiesel purification machine equipped with a cooling system. The cooling system aims to make the sedimentation process faster. The cooling system uses a thermoelectric module attached to a pipeline from the esterification tank to a purification tank. This machine is also equipped with a control system and valve driven by motor to perform the process automatically. The design of the biodiesel purification machine has been successfully developed and has followed a series of tests. The test results on the accuracy of flowmeters show that they work correctly. The application of a cooling system is proven to reduce the sedimentation process time to 20 minutes, which in turn shortens the time for the biodiesel purification process, which in turn shortens the time of the biodiesel purification process. In addition, the control system allows the machine to operate automatically, thereby reducing the operator's need significantly.